(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In online resources digital libraries are the focus of D-Lib Magazine, a journal indexed by theLibrary and Information Science Index (LISA). Given that it is a free magazine, it is also available toMizoram University students. When compared to other specialist journals in LISA’s index, D-LibMagazine’s SJR of 0.463 was above average. The researchers set out to examine the intellectual structureof academic journals by looking at their long-term publishing trends and subject organization. The studyanalyzed authorship patterns, cooperation tendencies, and cited references in final articles to get abetter picture of how productive institutions were throughout the time period under consideration.